Change mangement : - McCalman, James (SAGE, 2016)
The fourth edition of this highly successful textbook for change management uses current examples and a more strategic focus to guide students through the issues and processes associated with managing change. Now a classic in its field, the fourth edition of Change Management: a guide to effective implementation continues to offer readers highly practical strategies and step-by-step guidance for applying different models of change in different organizational scenarios. New to the Fourth Edition : A third expert author, Sabina Siebert, bringing a background in sociology and cultural studies An improved structure that consolidates all the existing strengths of the previous editions and separates the book into three parts, beginning with chapters assessing 'The Impact and Definition of Change', 'Implementation and Evaluation of Change' and ending with a critical outlook in 'Change Management - A Critical Perspective' A wealth of new and richly detailed case studies with an international and cross-cultural scope that draw upon different organization types, environments and perspectives for a diverse and global understanding of the current field of change management Two additional chapters on leading change and organisational culture, offering unparalleled coverage of managing systems and processes, combined with increased emphasis on managing human issues.